Oscillation-Based Spectroscopy for Cell-Culture Monitorization - Pérez, Pablo; Serrano-Viseas, Juan A.; Fernández-Scagliusi, Santiago; Martín-Fernández, Daniel; Huertas, Gloria; Yúfera, Alberto (Frontiers in Electronics, 2022)
Biological Impedance is a physical property related to the state and inherent evolution of biological samples. Among the existing impedance measurement methods, Oscillation-Based (OB) tests is a simple and smart solution to indirectly observe impedance. OB test requires some knowledge to tune the system blocks to specifications derived from every measure problem, looking for that the measurement sensitivity is optimum for the specific constraints imposed by the system under test, electronic interfaces and electrodes employed for test. In this way, the extension of these kind of measurement systems to spectroscopy enables a completely new range of applications for this technology without the restrictions imposed by setting a fixed frequency on the electrical oscillator.